Radio Listenership in Kathmandu - Shrestha, Shrijana (Communication Journal, 2022)
Radio plays a significant role in the Kathmandu society and that cannot be overlooked. The theories discussed for this study are uses and gratifications and media dependency theory. The data have been presented using frequency tables and charts. From this research work, it was discovered that the maximum number of respondents have gradually declined their interest and reliability on the radio today. The prevalence of web-based mediums has outdone the usage of radio and it has been reflected in this report as well. The goals are to investigate the current situation of radio listenership in Kathmandu, comprehend the evolution of listenership through time, and apprehend the prospects for radio listenership in the future. This study's findings revealed that the majority of respondents had seen a progressive fall in their interest in and dependability upon radio nowadays. Respondents' expectations for the future of radio in Kathmandu are apparently not very high. The predominance of web-based media has surpassed the use of radio, and this research confirms that. Finally, by the report's conclusion, we can also see how all the data were analyzed and presented, as well as some recommendations that could be used to raise the status of the radio.